Health technology assessment on super oxidized water for treatment of chronic wounds - Eftekharizadeh, Fereshteh (Med J Islam Repub Iran, 2016)
Background: Super oxidized water (SOW), as a novel antiseptic solution, is used with claims of effectiveness and cost effectiveness in healing chronic wounds such as diabetic foot, infectious postoperative ulcers and burn ulcers. We conducted a health technology assessment to evaluate the clinical evidence from clinical and randomized trials for this disinfection. This study aims to evaluate the safety, effectiveness and cost-effectiveness of this technology in Iran, for using as a wound disinfectant. Methods: Systematic literature searches were conducted from October 2013 to March 2014 for the following medical databases: OVID MEDLINE, CINAHL, the Cochrane Library and the PICO terms were included and then analyzed by Cochrane assessment criteria. Results: Out of 705 articles, twelve potentially relevant trials were identified. Others that didn’t come with the PICO criteria were excluded. 5 randomized controlled trials, 5 clinical trials, a rapid HTA and a case series that had studied the effectiveness of super oxidized water on patients with different chronic wounds, were included. Most of these trials were assessing similar sets of outcomes as the Safety and Effect on Healing days to re-epithelization, healing rate, effect on Infection bacterial counts and infection rates. Conclusion: Super oxidized water is a safe, effective and cost effective irrigation and cleansing agent due to the performed analysis in comparison with current treatment as povidone iodine for treating wound infections.